SXR rs3842689: a prognostic factor for steroid sensitivity or resistance in pediatric idiopathic nephrotic syndrome. (July 2016) - Turolo, Stefano; Edefonti, Alberto; Lepore, Marta; Ghio, Luciana; Cuzzoni, Eva; Decorti, Giuliana; Pasini, Andrea; Materassi, Marco; Malaventura, Cristina; Pugliese, Fabrizio; Montini, Giovanni
Aim: of the study was to analyse the impact of SXR rs3842689 polymorphism on the response to corticosteroids in pediatric idiopathic nephrotic syndrome.Patients & methods: 66 children (56 steroid-sensitive, ten steroid-resistant) were studied for SXR gene polymorphism distribution.Results: Steroid sensitive patients accounted for 96% of cases with In/In polymorphism, but only for 53% of cases with Del/Del polymorphism At odds ratio analysis, Del/Del represented a clear risk factor of steroid resistance (OR: 20.57; p = 0.009), while In/In was a favourable prognostic factor of steroid sensitivity.Conclusion: The analysis of SXR polymorphism is a promising tool to predict both the favourable response to corticosteroids and the risk of developing steroid resistance.